엇갈린 격자를 이용한 3차원 유한차분 시간영역 전자탐사 모델링 - 장한길로; Hangilro Jang; 남명진; Myung Jin Nam; 조성오; Sung Oh Cho; 김희준; Hee Joon Kim (지구물리와 물리탐사, 2017)
국내에서 시간영역 전자탐사(time-domain/transient electromagnetic, TEM) 자료의 해석은 1차원 알고리듬에 주로 의존하고 있는 실정이기 때문에 정밀한 해석을 위하여 3차원 모델링 및 역산 해석 프로그램의 개발이 필요한 상황이다. 이 연구에서는 엇갈린 격자를 이용한 시간영역 유한차분(staggered-grid finite-difference time-domain, FDTD)법에 기초하여 3차원 TEM 반응 모델링 알고리듬을 개발하였다. 시간영역 전자탐사의 모델링을 위해 맥스웰 방정식을 현시적 중앙점 FDTD법을 이용하여 이산화하였으며 수치 안정성을 높이기 위해 가상 변위전류항을 도입하였다. 일반적으로 많이 활용되는 소형코일 송신원을 수치적으로 구현하여 균질 반무한 공간에서의 해석해와 비교 검증하고 3차원 이상체에 대한 반응을 분석하였다. 이 연구에서 개발된 모델링 프로그램은 향후 TEM 전자탐사 자료의 정밀 해석에 기초가 될 것으로 기대한다. Interpretation of time-domain electromagnetic (TEM) data has been made mostly based on one-dimensional (1-D) inversion scheme in Korea. A proper interpretation of TEM data should employ 3-D TEM forward and inverse modeling algorithms. This study developed a 3-D TEM modeling algorithm using a finite difference time-domain (FDTD) method with staggered grid. In numerically solving Maxwell equations, fictitious displacement current is included based on an explicit FDTD method using a central difference approximation scheme. The developed modeling algorithm simulated a small-coil source configuration to be verified against analytic solutions for homogeneous half-space models. Further, TEM responses for a 3-D anomaly are modeled and analyzed. We expect that it will contribute greatly to the precise interpretation of TEM data.